2019
DOI: 10.1186/s13039-019-0425-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic identification of small supernumerary marker chromosomes using chromosome microarray analysis

Abstract: BackgroundThis study aimed to evaluate the feasibility of chromosomal microarray analysis (CMA) in detecting the origin and structure of small supernumerary marker chromosomes (sSMCs) in prenatal and postnatal cases and to clarify sSMC-related genotype-phenotype correlations.ResultsThirty-three cases carrying sSMCs were identified by banding cytogenetics. Of these cases, twenty-nine were first characterized by CMA and only two by FISH. The remaining two cases were excluded for their refusal to accept further e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Whole genomic DNA was extracted from amniocytes or fetal cord blood of each fetus and its parents using the QIAamp DNA Blood Mini Kit (Qiagen, Valencia, CA). The DNA was examined by SNP array analysis using the CytoScan 750 K Array (Affymetrix, Santa Clara, CA) containing 200,000 SNPs and 550,000 CNVs as previously described 13 . The results were analyzed using the Chromosome Analysis Suite software (Affymetrix) and annotated based on GRCh37 (hg19).…”
Section: Methodsmentioning
confidence: 99%
“…Whole genomic DNA was extracted from amniocytes or fetal cord blood of each fetus and its parents using the QIAamp DNA Blood Mini Kit (Qiagen, Valencia, CA). The DNA was examined by SNP array analysis using the CytoScan 750 K Array (Affymetrix, Santa Clara, CA) containing 200,000 SNPs and 550,000 CNVs as previously described 13 . The results were analyzed using the Chromosome Analysis Suite software (Affymetrix) and annotated based on GRCh37 (hg19).…”
Section: Methodsmentioning
confidence: 99%
“…G-banding analysis (C/NOR-banding when required) at a resolution of approximately 320~400 bands was performed on the parents’ peripheral fetal blood according to standard laboratory protocols and ISCN 2016 [14]. Around 2 ml of parental peripheral blood in the parents of the fetuses was collected in heparin tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Recently published studies indicated that the novel microarray methods such as CMA combined with molecular cytogenetic analysis is particularly effective in the rapid and accurate diagnosis of sSMCs or copy number variations. These combined protocols are especially useful in identifying rare structural chromosomal aberrations prenatally and in assessing the prognosis of fetuses carrying such abnormalities [29]. It is worth of noting that although aCGH identifies the whole gene component of sSMCs and the other underlying chromosomal anomalies too (except for balanced translocations) in one test, it may miss to diagnose sSMCs formed of heterochromatin and the cases with low level of mosaicism [30].…”
Section: Discussionmentioning
confidence: 99%